2011
DOI: 10.1108/08858621111179868
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of relationship marketing in international sponsorship networks

Abstract: PurposeWhile various scholars have identified relationship marketing objectives as a rationale for sports sponsorship engagement, analytic investigations of the implications of a relational approach to the corporate sponsorship network have been slow to materialize. The purpose of this paper is to advance the discussion of sponsorship as a means of industrial sports marketing towards a network conceptualization, which can be dissected from both the perspective of the sponsoring firms and that of the sponsored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 61 publications
2
46
0
1
Order By: Relevance
“…Accordingly, although business reasons dominate, social motives (such as a local interest in supporting professional sport) also seem to contribute to a sponsor's commitment to networks. The local commitment perspective of this study is unique to the field since most other studies on sponsor networks deal with international high-profile events with sponsors not linked to a local community (Cobbs, 2011;Morgan et al, 2014;Olkkonen, 2001). On the other hand, the sponsorship literature is rich in examples of community engagement and local commitment (Wagner and Nissen, 2015;Zinger and O´Reilly, 2010); thus, our study on local networks links the network literature to sponsorship research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, although business reasons dominate, social motives (such as a local interest in supporting professional sport) also seem to contribute to a sponsor's commitment to networks. The local commitment perspective of this study is unique to the field since most other studies on sponsor networks deal with international high-profile events with sponsors not linked to a local community (Cobbs, 2011;Morgan et al, 2014;Olkkonen, 2001). On the other hand, the sponsorship literature is rich in examples of community engagement and local commitment (Wagner and Nissen, 2015;Zinger and O´Reilly, 2010); thus, our study on local networks links the network literature to sponsorship research.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating a network related to a Formula One team, Cobbs (2011) shows that a relational network approach reveals new inter-organizational potentials for the sponsors. In a similar Morgan et al (2014) recently investigated an international sporting event in order to examine the relationship between the sporting event and its sponsors.…”
Section: From Consumer Orientation To Network Management: Insights Frmentioning
confidence: 99%
“…Inter-organizational Networks describe structures between organizations. In our review, Inter-organizational Networks were identified in two domains: 'Sport management' (Cobbs, 2011;Cousens et al, 2012;Sallent et al, 2011;Seevers et al, 2010) and 'Sport-related scientific literature ' (Agull o-Calatayud et al, 2008;Bruner et al, 2010;Love & Andrew, 2012;Quatman & Chelladurai, 2008a). While in the sport management studies relations among organization are analyzed, the studies on sport literature considered groups of authors and publications (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Wilkinson (1993) writes that the early days of sponsorship featured sponsorship primarily born of philanthropic ideals; companies did not see sponsorship as an important factor in achieving their business objectives. More recently, sponsorship research has shown companies place an increasing importance on the financial return of investment (Lough, 2000;Mullen, Hardy, & Sutton, 2014).Sport sponsorship has also evolved from its early foundations as a philanthropic act to a calculated corporate marketing tactic (Cobbs, 2011;Dolphin, 2003;Jensen and Cobbs, 2014;Lee, Hur, and Sung, 2015). Bennett (1977) writes that motivation is the driving force of behavior that causes individuals to act in a certain way so that needs will be fulfilled.…”
Section: Sponsorship As Supportmentioning
confidence: 99%